How Does Cross-Screen Visual Search Influence Visual Processing and Eye Movement Behavior Under Different Perceptual Window Conditions? - Yan, Biao; Wu, Xiaoli; Baber, Chris; Zhang, Lan; Liu, Xiao; Wu, Yuhan; Zhang, Xinyue; Wang, Zhiyu; Xu, Xun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
The increasing adoption of multi-screen systems in complex human–machine environments highlights the importance of understanding cross-screen visual search behavior for improving operational efficiency. However, the mechanisms underlying changes in visual processing and eye movement behavior during screen transitions remain insufficiently understood. This study employed a moving window paradigm to systematically investigate visual search performance and eye movement behavior during cross-screen visual search. A total of 20 participants completed visual search tasks in a simulated multi-display interface, while reaction time, fixation behavior, and area-of-interest (AOI) eye-tracking metrics were recorded. The results revealed significant effects of the perceptual-window condition on reaction time (p < 0.001), fixation duration (p < 0.001), and fixation count (p < 0.001). Reaction time decreased substantially from the 3° condition to the 5° condition, whereas only limited improvement was observed between the 5° and 7° conditions. Similarly, fixation duration and fixation count were significantly reduced under larger perceptual-window conditions, while no significant differences were found between the 5° and 7° conditions. These findings indicate a plateau effect in eye-movement-based visual processing efficiency beyond approximately 5°. Significant spatial orientation effects were also observed for reaction time (p < 0.001), time to first fixation (p < 0.001), and AOI visit count (p < 0.001). The east condition produced the longest reaction time and time to first fixation, whereas the west condition yielded the shortest reaction time. In contrast, the north condition showed the shortest time to first fixation and the highest AOI visit count, suggesting more efficient attentional engagement and visual exploration in the north region. Participants showed faster visual engagement and higher visit counts in the north region, followed by the west, while the east and south regions exhibited reduced visual sampling, indicating a stable spatial asymmetry in cross-screen visual search behavior. Although the north condition facilitated faster attentional engagement, the west condition yielded the shortest overall reaction time, suggesting partially distinct mechanisms between early attentional orientation and overall search efficiency. Overall, these findings indicate that cross-screen visual search dynamically influences visual processing and gaze allocation patterns under different perceptual-window constraints. The results provide empirical evidence for optimizing multi-display workstation design, control room interfaces, and complex monitoring systems, and offer a behavioral basis for improving information layout strategies in cross-screen operational environments.